Is weight gain associated with the incidence of periodontitis? A systematic review and meta‐analysis. (2nd June 2015) - Nascimento, Gustavo G.; Leite, Fábio R.M.; Do, Loc G.; Peres, Karen G.; Correa, Marcos B.; Demarco, Flávio F.; Peres, Marco A.
Abstract Aim This study aimed to conduct a systematic review assessing the effects of weight gain on the incidence of periodontitis in adults. Methods Electronic searches in four databases were performed up to and including February 2015. Only prospective longitudinal studies assessing the association between weight gain and the incidence of periodontitis in adults were eligible to be included in this study. All studies should state a clear description of nutritional status (Body Mass Index; Waist Circumference) as well as the case definition of periodontitis. Pooled relative risks (RR) for becoming overweight and obese on the incidence of periodontitis were estimated by meta‐analysis. Quality was assessed with the Newcastle–Ottawa scale for cohort studies. Results Five articles were included in this review and meta‐analysis with 42, 198 subjects enrolled. Subjects who became overweight and obese presented higher risk to develop new cases of periodontitis (RR 1.13; 95%CI 1.06–1.20 and RR 1.33 95%CI 1.21–1.47 respectively) compared with counterparts who stayed in normal weight. Conclusions A clear positive association between weight gain and new cases of periodontitis was found. However, these results are originated from limited evidence. Thus, more studies with longitudinal prospective design are needed.